Rodinný dům s provozovnou - Valtr, Filip (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Předmětem bakalářské práce je návrh rodinného domu s provozovnou. Jedná se o novostavbu izolovaného domu s plochou střešní konstrukcí ve městě Dobříš v ulici Bratří Čapků. Navrhovaný rodinný dům pro 4 osoby má dvě nadzemní podlaží, v přízemí se nachází garážové stání pro 1 osobní automobil. Je rozdělen na dva provozní celky a to rodinný dům a provozovna. Provozovna bude sloužit jako kancelář finančních poradců. Svislou nosnou konstrukci tvoří železobetonové sloupy, vodorovnou nosnou konstrukci tvoří železobetonové stropní desky a železobetonové trámy. Výplňové zdivo je z pórobetonových tvárnic Ytong. Opláštění provětrávané fasády je provedeno z desek Alucobond.

The subject of the bachelor’s thesis is a detached house design with business premises. It is a new building of an isolated house with a flat roof construction in the town Dobříš, in the Bratří Čapků Street. The designed detached house is for 4 persons; it has two aboveground floors and a garage with parking for one car on the ground floor. The house is divided in two operational units; the detached house and the business premises. The business premises will serve as a financial advisors’ office. Ferroconcrete pillars form the vertical supporting construction; ferroconcrete ceiling plates and ferroconcrete beams create the horizontal supporting construction. Beam filling is from aerated concrete blocks Ytong. The sheathing of the ventilated façade is from Alucobond desks.
Detached House with Business Premises
Keywords: Rodinný dům s provozovnou; rodinný dům; provozovna; Dobříš; ulice Bratří Čapků; finanční poradce; plochá střecha; provětrávaná fasáda; skeletový nosný systém; železobetonové stropní konstrukce; garáž; Alucobond; Detached house with business premises; detached house; business premises; Dobříš; Bratří Čapků street; financial advisor; flat roof; ventilated façade; skeleton supporting system; ferroconcrete ceiling construction; garage; Alucobond